Emerging two-dimensional nanostructured manganese-based materials for electrochemical energy storage: recent advances, mechanisms, challenges, and prospects. Issue 40 (6th October 2022) - Chen, Jun; Xu, Weili; Wang, Haoyu; Ren, Xuehua; Zhan, Feiyang; He, Qingqing; Wang, Huayu; Chen, Lingyun
Abstract : The review summarizes the progress of emerging 2D manganese-based materials as advanced electrode materials for EES. Abstract : By virtue of the prominent features of low cost, high surface area, wide potential window, high theoretical capacity and rich valence states, manganese (Mn)-based materials and their composites have attracted great interest as electrode materials for electrochemical energy storage (EES). Meanwhile, Mn-based materials with two-dimensional (2D) nanostructures have gained immense attention due to their larger specific surface area, which exposes active sites and increases the contact with the electrolyte. In the review, the several main categories of 2D nanostructured Mn-based materials including Mn-based oxides, hydroxides/layered double hydroxides (LDHs), sulfides, phosphides, and metal–organic frameworks (MOFs) are systematically introduced to offer a comprehensive overview about their structure and application for EES. Meanwhile, the recent advances in the investigation of their synthesis strategy, crystal structure, and electrochemical storage energy mechanism are summarized. Based on the relationship between the 2D nanostructure and electrochemical properties, their applications in supercapacitors (SCs), alkali (Li and Na)-ion batteries, and multivalent metal (Zn and Mg)-ion batteries (MIBs) are discussed in detail. Furthermore, this paper summarizes the representative strategies to overcome the bottlenecks of 2D nanostructured Mn-based materials for energy storage by introducing high conductivity materials, constructing advanced structures, and designing defect engineering. In addition, we discussed the challenges of 2D nanostructured Mn-based materials for SCs and MIBs and provided prospective insights for the future development of this research direction.